Der Jesusknabe verwandelt eine Lilie in eine Trompete - Kretzenbacher, Leopold (Traditiones (Ljubljana), 1999)
Proceeding from the apocryphal motif of Jesus reviving clay birds the author wishes to draw attention to a similar case from the Slovene song tradition, namely to two notations of the legendary song entitled Jezus spremeni lilijo vtrobento (Jesus Changes a Lily Into a Trumpet). He wonders which the flower mentioned in this song is.
Keywords: Ethnopoetics; ljudske pesmi; slovstvena folklora; nabožne pesmi